Cardiac Innervation and Sudden Cardiac Death. Issue 12 (5th June 2015) - Fukuda, Keiichi; Kanazawa, Hideaki; Aizawa, Yoshiyasu; Ardell, Jeffrey L.; Shivkumar, Kalyanam
Abstract : Afferent and efferent cardiac neurotransmission via the cardiac nerves intricately modulates nearly all physiological functions of the heart (chronotropy, dromotropy, lusitropy, and inotropy). Afferent information from the heart is transmitted to higher levels of the nervous system for processing (intrinsic cardiac nervous system, extracardiac-intrathoracic ganglia, spinal cord, brain stem, and higher centers), which ultimately results in efferent cardiomotor neural impulses (via the sympathetic and parasympathetic nerves). This system forms interacting feedback loops that provide physiological stability for maintaining normal rhythm and life-sustaining circulation. This system also ensures that there is fine-tuned regulation of sympathetic–parasympathetic balance in the heart under normal and stressed states in the short (beat to beat), intermediate (minutes to hours), and long term (days to years). This important neurovisceral/autonomic nervous system also plays a major role in the pathophysiology and progression of heart disease, including heart failure and arrhythmias leading to sudden cardiac death. Transdifferentiation of neurons in heart failure, functional denervation, cardiac and extracardiac neural remodeling has also been identified and characterized during the progression of disease. Recent advances in understanding the cellular and molecular processes governing innervation and the functional control of the myocardium in health and disease provide a rational mechanistic basis for the development of neuraxial therapies for preventing sudden cardiac death and other arrhythmias. Advances in cellular, molecular, and bioengineering realms have underscored the emergence of this area as an important avenue of scientific inquiry and therapeutic intervention.